Quantifying the rear and front long-term spectral impact on bifacial photovoltaic modules - Mouhib, Elmehdi; Rodrigo, Pedro M.; Micheli, Leonardo; Fernández, Eduardo F.; Almonacid, Florencia (My University, 2022)
The demand for bifacial photovoltaic modules is continuously increasing. However, some aspects of their behaviour under realistic operating conditions still require more in-depth investigations. Indeed, the long-term analysis of the spectral impact on bifacial modules remains pending. This is particularly true for the rear incident spectrum, which changes depending on the ground type. In this paper, the rear and front long-term spectral impact on bifacial modules is analysed for three locations (Tabernas, Spain; Solar Village, Saudi Arabia; Alta Floresta, Brazil) and four ground types (light soil, white sand, green grass, and concrete slab) at daily, monthly and annual timescales. The SMARTS model is used to generate front and ground-reflected annual spectra. The investigation leads to the definition of a novel metric, called bifacial spectral factor, which quantifies the combined front and rear spectral impact. Results show that the annual bifacial spectral impact differs from the monofacial one due to the influence of the rear spectral irradiance. Green grass is found to have the higher bifacial spectral benefit, leading to yields in between 1.19% and 1.65% higher than in the monofacial case. However, thanks to its high albedo coefficient, white sand is the most convenient ground among the analysed types in terms of bifacial spectral energy gains. The rear spectral factor shows a great range of variation as a function of ground type (between 0.989 and 1.150). However, this is only a non-negiglible second order effect compared to the bifacial spectral factor, which is mainly influenced by the front spectral factor.